2022
DOI: 10.1038/s41598-022-11002-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal male reproduction and embryonic development induced by downregulation of a phospholipid fatty acid-introducing enzyme Lpgat1 in zebrafish

Abstract: Phospholipids in the membrane consist of diverse pairs of fatty acids bound to a glycerol backbone. The biological significance of the diversity, however, remains mostly unclear. Part of this diversity is due to lysophospholipid acyltransferases (LPLATs), which introduce a fatty acid into lysophospholipids. The human genome has 14 LPLATs and most of them are highly conserved in vertebrates. Here, we analyzed the function of one of these enzymes, lysophosphatidylglycerol acyltransferase 1 (Lpgat1), in zebrafish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…established zebrafish mutants of LPLAT7/LPGAT1 and showed that they had decreased levels of C18:0-containing PC and PE and increased levels of C16:0-containing PC and PE. PG species were not affected in the lplat7 / lpgat1 mutant zebrafish ( 23 ).…”
Section: Discussionmentioning
confidence: 98%
“…established zebrafish mutants of LPLAT7/LPGAT1 and showed that they had decreased levels of C18:0-containing PC and PE and increased levels of C16:0-containing PC and PE. PG species were not affected in the lplat7 / lpgat1 mutant zebrafish ( 23 ).…”
Section: Discussionmentioning
confidence: 98%
“…The diversity of phospholipids due to variations in the polar head group and fatty acids, as determined by LPLATs, has been reported 39,[46][47][48] ; however, phospholipid profiles determined by LPLAT10 in vivo have not been elucidated. Our study is the first to reveal PC and LPC profiles determined by LPLAT10 in the mouse liver using an Ad vector-mediated overexpression system.…”
Section: Discussionmentioning
confidence: 99%
“…PS signaling and recognition by receptors are essential for normal zebrafish embryo development [ 90 ] and studies have shown that dysregulation of PS levels can be associated with morphological malformations similar to those seen in this study. Shibata et al [ 91 ] found that downregulation of lysophosphatidylglycerol acyltransferase 1 resulted in decreases in various phospholipids, including PS, that coincided with developmental malformations in zebrafish, including bent embryo axis (spinal curvature). Dysregulation of phosphatidylserine synthase (PSS), which catalyzes the production of PS, has been linked to skeletal malformations in humans and severe angulation of the trunk (spinal curvature) in zebrafish [ 92 ].…”
Section: Discussionmentioning
confidence: 99%